Immobilization technique for toxic sludge. - Peralta, Genandrialene L.
High concentrations of heavy metals such as Ag, As, Cd, Cr, Hg and Pb in a sludge generated from a cooling tower can not be directly disposed of in a sanitary landfill without risking groundwater contamination. Preliminary studies on the sludge show that the heavy metal concentrations are beyond the standards set by the USEPA. This necessitates the treatment of the sludge prior to final disposal. The solidification technique was employed to immobilize the contaminants to a degree where it no longer poses an environmental hazard. The technique utilized silica-rich materials such as portland cement and rice hull ash as immobilizing agents. Simulation studies of the behavior of the treated sludge during long term storage showed significant reduction in heavy metal mobility to within the standards. X-ray diffraction (XRD) analysis of the cementitious product point to physical entrapment of the heavy metals within the ettringite/silicate matrix as the main immobilizing mechanism.